The difference between residual monomer dentin bonding HEMA and UDMA with acetone and ethanol solvent after binding to type I collagen - N. Normayanti; Adioro Soetojo; Nirawati Pribadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: In caries and non-caries lesions involving dentine, it is necessary to provide dentine-bonding material to help improve retention between the composite resin and the tooth surface. Composite resin attachment to dentine is influenced by bonding polymerization reactions. In several studies, researchers found that polymerized monomers will experience volume shrinkage because not all will fully polymerize but, rather, become residual monomers that can cause post-operative pain. Purpose: This study aimed to identify the difference in the amount of residual monomers between HEMA- and UDMA-based dentin bonding materials with acetone and ethanol solvents after binding to type I collagen. Methods: Four groups featured in this study: HEMA with acetone solvent and type I collagen , HEMA with ethanol solvent and type I collagen , UDMA with acetone solvent and type I collagen and UDMA with ethanol solvent and type I collagen . All groups were checked by high performance liquid chromatography (HPLC) to quantify the remaining amount of monomers. Results: The percentage of residual monomers of dentine bonding HEMA with acetone solvent and type I collagen was 10.69%, HEMA with ethanol solvent and type I collagen was 13.93%, UDMA with acetone solvent and type I collagen was 2.89% and UDMA with ethanol solvent and type I collagen was 7.48%. Conclusion: HEMA with ethanol solvent has the highest number of residual monomers, while UDMA with acetone solvent has the lowest.